Macrophage Migration Inhibitory Factor in the Paraventricular Nucleus Plays a Major Role in the Sympathoexcitatory Response to Salt - Colombari, Eduardo (2010)
Central hyperosmotic stimulation (HS) evokes increases in sympathetic nerve activity mediated by activation of angiotensin type 1 receptors in the hypothalamic paraventricular nucleus (PVN). Macrophage inhibitory migration factor (MIF) is an intracellular inhibitory regulator of angiotensin type 1 receptor–mediated actions of angiotensin II within neurons of the PVN. MIF mediates its actions via its intrinsic thiol-protein oxidoreductase activity. We demonstrate that intracerebroventricular injection of hypertonic saline into Sprague-Dawley rats elicits a significant (≈112%) increase in MIF mRNA expression in the PVN. Next, we evaluated the effect of viral-mediated expression of either MIF or [C60S]-MIF (which lacks thiol-protein oxidoreductase activity) in the PVN on the sympathoexcitation evoked by HS. We used a decorticate, arterially perfused in situ preparation of male Wistar rats (60 to 80 g). HS was induced by raising perfusate osmolality from 290 to 380 milliosmoles for 40 seconds. Seven to 10 days before experiments, rats were injected bilaterally (500 nL per side) with 0.9% saline (control) or with adenoassociated virus to express MIF, [C60S]-MIF, or enhanced green fluorescent protein in the PVN. HS produced sympathoexcitation in both the 0.9% saline and enhanced green fluorescent protein groups (sympathetic nerve activity increase of +27±4% and +25±4%, respectively; P<0.05), an effect that was not observed in the MIF group (+4±5%). Conversely, the HS-induced increase in sympathetic nerve activity was potentiated in the [C60S]-MIF group (+45±6%; P<0.05). We propose that MIF acting within the PVN is a major counterregulator of HS-induced sympathoexcitation, an effect that depends on thiol-protein oxidoreductase activity.